2022
DOI: 10.7454/jki.v25i2.847
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Father’s Behavior in Preventing Childhood Stunting Based on Health Belief Model

Abstract: Childhood stunting is still a significant public health burden in Indonesia. Fathers' engagement in childcare could improve a child's health and help to prevent stunting. This study aimed to analyse factors related to the father's behaviour in preventing childhood stunting based on Health Belief Model. This study was used a correlational study design with a cross-sectional approach. This study involved 199 fathers who had children under five years old, recorded at Puskesmas (Public Health Center) Maronggela, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…On the basis of their findings, Faye, Fonn, and Kimani-Murage (2019) suggest that if fathers of stunted children knew more about what foods children need to eat for healthy growth, they may be more likely to provide appropriate foods within the financial resources they have available. Another approach is suggested in study at Puskesmas (Public Health Center) Maronggela, East Nusa Tenggara, Indonesia showed fathers’ behavior in preventing stunting in toddlers is related to their perception of a disease and cues that can trigger decision-making processes related to actions to prevent child stunting ( Has et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of their findings, Faye, Fonn, and Kimani-Murage (2019) suggest that if fathers of stunted children knew more about what foods children need to eat for healthy growth, they may be more likely to provide appropriate foods within the financial resources they have available. Another approach is suggested in study at Puskesmas (Public Health Center) Maronggela, East Nusa Tenggara, Indonesia showed fathers’ behavior in preventing stunting in toddlers is related to their perception of a disease and cues that can trigger decision-making processes related to actions to prevent child stunting ( Has et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%